2017
DOI: 10.1038/s41598-017-00217-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence suggests that specular reflectance and glossy appearance help amplify warning signals

Abstract: Specular reflection appears as a bright spot or highlight on any smooth glossy convex surface and is caused by a near mirror-like reflectance off the surface. Convex shapes always provide the ideal geometry for highlights, areas of very strong reflectance, regardless of the orientation of the surface or position of the receiver. Despite highlights and glossy appearance being common in chemically defended insects, their potential signalling function is unknown. We tested the role of highlights in warning colour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
2
24
1
Order By: Relevance
“…The combination of red and black elements is a textbook example of aposematic coloration (Endler and Mappes 2004), but the monotonous metallic colouration was as effective as light red-and-black pattern in our experiments in terms of predator avoidance learning and signal memorability. A metallic lustre is generally interpreted as a warning signal (Borer et al 2010), but studies of bird responses to iridescence are scarce and the findings are contradictory: some, including our study, have demonstrated that iridescence itself enhances avoidance learning, (Fabricant et al 2014;Waldron et al 2017) while others have reported no effects of prey iridescence on bird attack rates (Pegram et al 2015). This discrepancy may indicate that bird responses to iridescent coloration of prey are idiosyncratic.…”
Section: Chemical Defence Of C Lapponica Against Bird Predatorscontrasting
confidence: 81%
“…The combination of red and black elements is a textbook example of aposematic coloration (Endler and Mappes 2004), but the monotonous metallic colouration was as effective as light red-and-black pattern in our experiments in terms of predator avoidance learning and signal memorability. A metallic lustre is generally interpreted as a warning signal (Borer et al 2010), but studies of bird responses to iridescence are scarce and the findings are contradictory: some, including our study, have demonstrated that iridescence itself enhances avoidance learning, (Fabricant et al 2014;Waldron et al 2017) while others have reported no effects of prey iridescence on bird attack rates (Pegram et al 2015). This discrepancy may indicate that bird responses to iridescent coloration of prey are idiosyncratic.…”
Section: Chemical Defence Of C Lapponica Against Bird Predatorscontrasting
confidence: 81%
“…Importantly, iridescence is found in nonreproductive stages, such as caterpillars and butterfly chrysalises [13,14]. Here, sexual selection seems unlikely, although a warning role (aposematism) is certainly possible [15,16]. Instead, the ''father of camouflage,'' Abbott Thayer [2], suggested that iridescence in many animals is actually camouflage, because the directionality of color in iridescent animals makes them appear ''dissolved into many depths and distances'' (p. 87).…”
Section: Resultsmentioning
confidence: 99%
“…Luminance is especially important in the spatial vision of birds (Stevens & Cuthill, 2006), and birds generally avoid objects with high reflectance. For example, tits show an initial avoidance of glossy prey (Doktorovová et al, 2019;Waldron et al, 2017). The brightness contrast between prey and background, rather than the color contrast, may function as a warning signal also for color-blind predators (Prudic, Skemp, & Papaj, 2007).…”
Section: Effects Of Model Color On Predator Attacksmentioning
confidence: 99%